Functional Outcome of Patients Undergoing Knee Arthrodesis after Infected Total Arthroplasty - Vivacqua, Thiago; Moraes, Rui; Barretto, João; Cavanelas, Naasson; Albuquerque, Rodrigo; Mozella, Alan (Revista Brasileira de Ortopedia, 2020)
Objective Retrospectively assess the functional outcome of patients undergoing arthrodesis after septic failure of total knee arthroplasty.Methods Eighteen patients were evaluated, with a mean time of 3.7 years of follow-up. Arthrodesis surgery was performed using a narrow anterior dynamic compression plate, and medial or external fixator in two planes of the joint (Orthofix Bone Growth Therapy, Lewisville, TS, USA), at the surgeon's discretion.Results The most frequent pathogen found was Staphylococcus aureus methicillin sensitive (38.9%). The mean lower limb discrepancy was 3.63 cm. The mean knee society score was 68 points. According to the visual analog scale for pain, 44% of the patients had a 0 score at the time of assessment, and 22.2% were very dissatisfied, despite the bone healing achieved. Patients were assessed for the ability to walk with or without assistance.Conclusion Knee arthrodesis surgery was effective in controlling the infectious process and decreasing pain complaints, but satisfaction with the procedure was low.
Keywords: arthrodesis; knee; arthroplasty, replacement, knee; infection